Pendidikan Karakter Anak Usia Dini Melalui Pengenalan Asmaul Husna Menggunakan Gaya Belajar Auditori : doi 10.58569/jies.v1i2.579 - Kinanti, Putri; Legi Sasdini, Helen; Fajrussalam, Hisny; Dwi Alpaini, Shaumi (Journal of Islamic Education Studies, 2023)
One of the basic needs of the community is character education, this study aims to introduce Asmaul Husna to early childhood through auditory learning styles. This research uses class action research method (classroom action research). Data collection techniques were carried out through interviews and observations on group B children aged 5-6 years in KB Dar uluum as many as 23 students consisting of 11 boys and 12 girls. Based on the results of the study, it was obtained that the pre-cycle acquisition resulted in an increase of 68% in cycle 1 by 25% to 40%, then in cycle 2 it increased by 20% to 60%. Based on the percentage of achievement from this study, the hypothesis is accepted. So it can be concluded that through the auditory learning style can make it easier for children to recognize Asmaul Husna. Through this study, the researchers concluded that one way to quickly introduce Asmaul Husna is through the auditory learning style.